A Metabolomics Approach to Improving CHO Cell Productivity - Yao, Grace. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Kyongbum Lee.; Committee: Rebecca Scheck, Emmanuel Tzanakakis, and Michael Borys.; Keywords: Bioengineering, Bioinformatics, and Cellular biology.